PLANNING AND SCHEDULING IN AUTOMATIC TRAIN SIGNALING MAINTENANCE: A REVIEW - Raharjo, Rachmad Dwi; Wicaksono, Satrio; Budiwantoro, Bagus (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The development of automatic railway signaling systems that use moving block systems has grown rapidly. The moving block signaling system, which is a development of the fixed block system, has functions such as automatic control, shortening headways, increasing operating capacity, and railway safety. The Technology used in the moving block signaling system must be reliable and suitable for passenger comfort and safety. So, an effective and efficient maintenance method is needed. Planned and scheduled maintenance prevents disruption and gives minimum maintenance costs. The condition-based maintenance, on the other hand, is the right maintenance for an automatic train signaling system because it uses a data-driven model so that it can support decisions in determining maintenance strategies, and maintenance can be optimized using the Reliability, Availability, Maintainability, and Safety (RAMS) method with one of the Reliability Centered Maintenance (RCM) analysis tools. This optimization can increase operational safety, maintenance cost efficiency, and asset availability. In addition, another advantage of this RCM method is that it can identify critical components that require maintenance priority, so that maintenance resources can be optimized.